2019
DOI: 10.1039/c9ra02429h
|View full text |Cite
|
Sign up to set email alerts
|

Modulating and opposite actions of two aqueous extracts prepared fromCinnamomum cassiaL. bark andQuercus ilexL. on the gastrointestinal tract in rats

Abstract: Cinnamon bark and evergreen oak acorns, natural sources of functional ingredients, are effective for those suffering from diarrhea, constipation and irritable bowel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Among these laurel-derived ligands, lauruside 5 emerged from our study as the most promising candidate as a potential M pro inhibitor. Moreover, despite its lower binding affinity for the protease when compared to lauruside 5, kaempferol, a natural compound isolated not only from Laurus nobilis L. but also from other Mediterranean plants like Quercus Ilex L. (Sebai et al 2019 ), especially in glucosidated form (Karioti et al 2010 ), could act as a potentially effective M pro inhibitor. Remarkably, still showing an interesting predicted binding energy (− 7.4 kcal/mol for the top scoring pose), it is also endowed with an even more favourable predicted toxicity profile (Class V) than laurusides.…”
Section: Discussionmentioning
confidence: 99%
“…Among these laurel-derived ligands, lauruside 5 emerged from our study as the most promising candidate as a potential M pro inhibitor. Moreover, despite its lower binding affinity for the protease when compared to lauruside 5, kaempferol, a natural compound isolated not only from Laurus nobilis L. but also from other Mediterranean plants like Quercus Ilex L. (Sebai et al 2019 ), especially in glucosidated form (Karioti et al 2010 ), could act as a potentially effective M pro inhibitor. Remarkably, still showing an interesting predicted binding energy (− 7.4 kcal/mol for the top scoring pose), it is also endowed with an even more favourable predicted toxicity profile (Class V) than laurusides.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this action of pacemaker potentiality depolarization could produce a GI-motility increase, as with diverse medicinal plants like Liriope platyphylla and Citrus unshiu. 59 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, this action of pacemaker potentiality depolarization could produce a GI-motility increase, as with diverse medicinal plants like Liriope platyphylla and Citrus unshiu. 59 Decreased mucus generation in the mucosa of the colon is related with colonic slow transit and noted to reduce the colonic mucosal layer thickness, and the number of mucus-generating cells has been investigated by histopathological diagnosis in the constipated animals. In this context, in the treatment of animals with LP for a week, an alteration in the colon microscopical structure was detected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, tannins, which are present in cassia bark extract, are able to reduce the demand for food intake by delaying the digestion action and by delaying the digestive track emptying. Researchers have reported that cassia bark extract is helpful in different GI-related disorders like constipation, and diarrhea [ 815 ]…”
Section: Health Benefit Potentialmentioning
confidence: 99%